Analysis of The Effect of Policy Evaluation on Improving the Quality of Islamic Education at MTS Al-Mahmud Aik Ampat - Utama, Wahyudi; Nasir, Mohamad Abdun; Tahir, M (Institut Agama Islam Negeri (IAIN) Curup, 2024)
The purpose of this study was to explain the effect of policy evaluation on the quality of Islamic education at MTs Al-Mahmud Aik Ampat. This research uses quantitative type with analytic design. The population of this study were all teachers and students of MTs Al-Mahmud Aik Ampat and the sample was 13 teachers and 13 students. the sampling technique used was random sampling. Data collection techniques through observation with questionnaire instruments for policy evaluation and quality of Islamic education. Data analysis techniques using t test and or F test. The results showed that there was an effect of policy evaluation on the quality of Islamic education at MTs Al-Mahmud Aik Ampat as seen from the significant value obtained in the t test and F test 0.005 is smaller than 0.05. This means that Ha is accepted and Ho is rejected. This evaluation can help MTs Al Mahmud to correct ineffective education policies. This is crucial to ensure that the quality of education produced by MTs Al Mahmud remains high and relevant to students' needs.